Feasibility of transabdominal Doppler ultrasonography for studying ovarian blood flow characteristics in cycling gilts - Stark, Rosa; Herlt, Catherine; Sigmarsson, Haukur L.; Kauffold, Johannes (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2019)
Objective The aim of this study was to assess ovarian blood flow characteristics by applying transabdominal color Doppler ultrasonography during the course of the estrous cycle in gilts.Materials and methods Estrus and ovulation were synchronized in 15 pubertal gilts. During their consecutive spontaneous estrous cycle the gilts were sonographically scanned daily and ovarian blood flow was determined by imaging perfused areas of the ovarian hilus and the ovarian tissue. Recorded video clips were then analyzed for the parameters perfused area (Amix), blood flow velocity (vmix) as well as resistance (RIvmix) and pulsatility index (PIvmix) using the software PixelFlux®.Results All blood flow parameters showed an estrous cycle dependent course, with Amix and vmix being highest in diestrus, followed by proestrus, while RIvmix and PIvmix patterns were inversely proportional.Conclusion and clinical relevance Transabdominal color Doppler ultrasonography proved feasible to study ovarian perfusion characteristics in pubertal gilts. The ovarian blood flow was dependent on the stage of estrous cycle and highest in diestrus. The results of this study encourage the use of color Doppler ultrasonography to also investigate reasons of ovary-caused infertility including corpus luteum insufficiency or seasonal effects on ovary function.
Keywords: Gilts; estrous cycle; ovarian perfusion; color Doppler ultrasonography